Compassion satisfaction and compassion fatigue in frontline nurses during the COVID‐19 pandemic in Wuhan, China - Xia, Wang; Defang, Wu; Xiaoli, Guan; Jinrui, Cui; Weidi, Wang; Junya, Liu; Luhong, Hu; Hui, Wang (Journal of nursing management, 2022)
Aim The aim of this study is to investigate the compassion satisfaction and compassion fatigue among Chinese frontline nurses during the COVID‐19 pandemic in Wuhan, China and to explore the related factors. Background Frontline nurses undertake a huge nursing workload with a risk of infection, causing great pressure on them and making them face a risk of compassion fatigue during the pandemic. Methods A cross‐sectional online survey was conducted from 9 March to 15 March 2020. A total of 1582 nurses caring for critical patients with COVID‐19 participated. Compassion satisfaction and compassion fatigue (comprising burnout and secondary traumatic stress) were assessed with the Professional Quality of Life Scale, and resilience was measured with the Chinese 10‐item Connor‐Davidson Resilience Scale. Results Moderate levels of compassion satisfaction (36.99 ± 6.71), burnout (24.14 ± 5.33) and secondary traumatic stress (24.53 ± 5.24) were experienced by frontline nurses. Resilience and perceived work pressure were the main predictors. Conclusions Frontline nurses demonstrated a moderate level of compassion satisfaction and compassion fatigue. Implications for nursing management The compassion fatigue of frontline nurses should be considered. Strategies aiming to reduce stress and enhance resilience, such as training about psychological adjustment, developing professional skills and creating a supportive workplace environment, are several options. The trial is not registered. This study is a cross‐sectional study, and according to China's clinical trial registration standards, such studies are not required to be registered. So the trial is not registered. However, oral consent was obtained from the ethics committee of the hospital before this study was conducted.